The Effect of Residing Altitude on Levels of High-Density Lipoprotein Cholesterol: A Pilot Study From the Omani Arab Population. (July 2015) - Al Riyami, Nafila B.; Banerjee, Yajnavalka; Al-Waili, Khalid; Rizvi, Syed G.; Al-Yahyaee, Said; Hassan, Mohammed O.; Albarwani, Sulayma; Al-Rasadi, Khalid; Bayoumi, Riad A.
Lower mortality rates from coronary heart disease and higher levels of serum high-density lipoprotein cholesterol (HDL-C) have been observed in populations residing at high altitude. However, this effect has not been investigated in Arab populations, which exhibit considerable genetic homogeneity. We assessed the relationship between residing altitude and HDL-C in 2 genetically similar Omani Arab populations residing at different altitudes. The association between the levels of HDL-C and other metabolic parameters was also investigated. The levels of HDL-C were significantly higher in the high-altitude group compared with the low-altitude group. Stepwise regression analysis showed that altitude was the most significant factor affecting HDL-C, followed by gender, serum triglycerides, and finally the 2-hour postprandial plasma glucose. This finding is consistent with previously published studies from other populations and should be taken into consideration when comparing cardiovascular risk factors in populations residing at different altitudes.